Numerical prediction of dynamic stability loss of a flexible cylindrical shell in a granular medium - Paweł Szklennik; Grzegorz Bąk (Biuletyn Wojskowej Akademii Technicznej, 2019)
The paper presents an application of the discrete element method for an analysis of dynamical stability loss of the flexible cylindrical shell section interacting with a model granular medium. The main scope was to investigate the forms of dynamical stability loss, considering finite displacements. The granular medium weight and additional external load transmitted from the surface were considered with different backfill height over the cylindrical shell. Application of a discrete model enables to consider random imperfections in the granular medium structure. It is shown that imperfections of a granular soil structure occurring in a close surrounding of the shell have an essential impact on the shell deformations. Numerical modelling, using the discrete element method, enables to obtain solutions of dynamic interaction by investigating finite two dimensional deformations. Keywords: discrete element method, cylindrical shell, granular medium, stability